Analisis Penerapan Akuntansi Obligasi Syariah (Sukuk) Berdasarkan PSAK 110 pada PT Bank Muamalat Indonesia Tbk - Setiyawati, Amilia; Elza Mariska; Subaidah; Megania Kharisma (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2026)
The development of the Islamic capital market in Indonesia has encouraged the increased use of Islamic bonds (sukuk) by Islamic financial institutions. However, in practice, the application of sukuk accounting still has the potential for discrepancies due to the differences in characteristics between sukuk and conventional bonds. This study aims to analyze the application of Islamic bond (sukuk) accounting based on Statement of Financial Accounting Standards (PSAK) 110 at PT Bank Muamalat Indonesia Tbk. This study uses a qualitative descriptive method with a case study approach. The data used are secondary data obtained from the financial statements and annual reports of PT Bank Muamalat Indonesia and other supporting literature. Data analysis techniques were conducted by comparing the company’s sukuk accounting practices with the provisions of PSAK 110, which covers aspects of recognition, measurement, presentation, and disclosure. The results show that, in general, PT Bank Muamalat Indonesia Tbk has implemented sukuk accounting in accordance with PSAK 110, particularly in the aspects of recognition, measurement, and presentation. However, disclosure aspects still require improvement, particularly regarding explanations of contract types, sukuk structures, and inherent risks. This research is expected to contribute to the development of sukuk accounting practices and serve as a reference for further research in the field of sharia accounting.